Implementation of The Independent Curriculum in Indonesian Language Learning at Primary School - Roby, Muhammad; Aulia, Nur Sufi; Suherman, Ria (Journal of General Education Science, 2023)
This research examines the implementation of the Independent Curriculum in teaching Indonesian at SD Negeri 058379 Otorita. This research uses a qualitative approach, focusing on the challenges faced by fourth grade teachers in managing students with diverse interests. Findings indicate difficulties in maintaining order due to differences in interests among students. The Independent Curriculum's emphasis on differentiation requires effective strategies in accommodating this diversity. The proposed solution includes improvements to school facilities and infrastructure, along with comprehensive outreach efforts. This analysis emphasizes the importance of overcoming these challenges to increase the effectiveness of the Merdeka Curriculum, especially in the context of language education at the primary level.